2022
DOI: 10.3390/w14091476
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Car Wash Wastewater Treatment by Cyclo-Flow Filtration

Abstract: With the increase in transportation demand and facilities in this era and the significant improvement in people’s living standards, the annual production and sales of vehicles are steadily increasing. With this, the issues of car wash wastewater treatment and water pollution are becoming more and more serious. Car wash wastewater mainly comprises fine sand, slick oil, suspended solids (SS), and surfactants, and can be quantified as chemical oxygen demand (COD) on a normative basis. This study examines the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Therefore, the treatment of these effluents has become an eminent need on a global scale. 28,29 Was reported that 30 by 2020, there were estimated to be 1.5 billion vehicles on the planet; and, if they were washed just once a month, 1.8 billion tons of wastewater would be generated from the water used in these operations, enough to serve 33 million people and costing $1.8 billion annually. The authors highlight that this volume represents the total consumption of the population of Malaysia, Venezuela, the Republic of Ghana, Oceania (including Australia and New Zealand), or the combined population of Denmark, Norway, Switzerland, Finland, and Iceland.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the treatment of these effluents has become an eminent need on a global scale. 28,29 Was reported that 30 by 2020, there were estimated to be 1.5 billion vehicles on the planet; and, if they were washed just once a month, 1.8 billion tons of wastewater would be generated from the water used in these operations, enough to serve 33 million people and costing $1.8 billion annually. The authors highlight that this volume represents the total consumption of the population of Malaysia, Venezuela, the Republic of Ghana, Oceania (including Australia and New Zealand), or the combined population of Denmark, Norway, Switzerland, Finland, and Iceland.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, the increase in transport facilities and the improvement of the standard of living of people have driven the acquisition of vehicles and, with this, the vehicle wash activities have increased expressively and, consequently, the volume of effluents generated in this activity has increased expressively. Therefore, the treatment of these effluents has become an eminent need on a global scale. , Was reported that by 2020, there were estimated to be 1.5 billion vehicles on the planet; and, if they were washed just once a month, 1.8 billion tons of wastewater would be generated from the water used in these operations, enough to serve 33 million people and costing $1.8 billion annually. The authors highlight that this volume represents the total consumption of the population of Malaysia, Venezuela, the Republic of Ghana, Oceania (including Australia and New Zealand), or the combined population of Denmark, Norway, Switzerland, Finland, and Iceland.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the remaining oil content is small, and standards are usually met, allowing for such pre-treated wastewater to be discharged to the municipal sewage treatment plant. According to the requirements of some countries, a significant portion of the water should be treated and returned to car washing [21,22]. In this case, the application of the UF process is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…More than 100–200 L of water is used to wash a car, which gives an annual worldwide consumption of millions of cubic meters [ 5 , 8 ]. For this reason, in some countries, legal regulations require that 40–80% of the water should be recovered for washing cars [ 9 , 10 ]. Such possibilities are created by membrane processes [ 8 , 11 , 12 ], which also allow the construction of small installations that can be used in manual car washes.…”
Section: Introductionmentioning
confidence: 99%